Peningkatan Hasil Belajar IPS Melalui Model Pembelajaran Two Stay Two Stray - Murni, Tri (JURNAL PENA EDUKASI, 2018)
Abstract: This study is based on the problems: (a) Improving Student Learning Out-comes in IPS Subject Materials Excellence Location and Life of Indonesian Society Through Two Stay-Two Stray Learning Model For Students of Class VIII.9 SMP Negeri 1 Kisaran academic year 2017/2018 While the purpose of research These are: To find out whether the application of the Two Stay-Two Stray learning model can improve the learning outcomes in the subjects of social studies materials Excellence Location and Life of Indonesian Society of VIII.9 students SMP Negeri 1 Kisaran academic year 2017/2018Subjects of this research is student of class VIII.9 SMP Negeri 1 Kisaran year lesson 2017/2018. Data obtained in the form of formative test results, observation sheet of teaching and learning activities. From the analysis results obtained that student achievement increased from cycle I to cycle II, that is cycle I (67,65%) and cycle II (91,18%). The conclusion of this study is the application of Two Stay-Two Stray learning model Can improve the learning out-comes in the subjects of Social Studies materials Excellence Location and Life Indonesian Society students class VIII.9 SMP Negeri 1 Kisaran academic year 2017/2018. Keywords: two stay two stray, Indonesian people Abstrak: Penelitian ini berdasarkan permasalahan : (a) Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPS Materi Keunggulan Lokasi dan Kehidupan Masyarakat Indonesia Melalui Model Pembelajaran Two Stay-Two Stray Bagi Siswa Kelas VIII.9 SMP Negeri 1 Kisaran Tahun Pelajaran 2017/2018 Sedangkan tujuan dari penelitian ini adalah: Untuk mengetahui Apakah penerapan model pembelajaran Two Stay-Two Stray Dapat meningkatkan hasil belajar pada mata pelajaran IPS materi Keunggulan Lokasi dan Kehidupan Masyarakat Indonesia siswa kelas VIII.9 SMP Negeri 1 Kisaran Tahun Pelajaran 2017/2018. Subjek penelitian ini adalah siswa kelas VIII.9 SMP Negeri 1 Kisaran tahun pelajaran 2017/2018. Data yang diperoleh berupa hasil tes formatif, lembar observasi kegiatan belajar mengajar. Dari hasil analisis didapatkan bahwa prestasi belajar siswa mengalami peningkatan dari siklus I sampai siklus II, yaitu siklus I (67,65%) dan siklus II (91,18%). Kesimpulan dari penelitian ini adalah penerapan model pembelajaran Two Stay-Two Stray Dapat meningkatkan Hasil belajar pada mata pelajaran IPS materi Keunggulan Lokasi dan Kehidupan Masyarakat Indonesia siswa kelas VIII.9 SMP Negeri 1 Kisaran Tahun Pelajaran 2017/2018. Kata kunci: two stay two stray, masyarakat Indonesia